Impact of voltage-accelerated stress on hole trapping at operating condition - Tung, Zhi Yan (2018)
This letter shows that voltage-accelerated stressing (VAS), a common methodology used in gate-oxide reliability testing, can change the capture activity of a time-zero oxide trap (i.e., already active under operating condition). It is found that after VAS, a time-zero oxide trap can be rendered either significantly more or less likely to capture a hole, implying that the applied electrical stress may have changed the atomic structure of the trap. The question on whether such change is relevant to reliability testing would have to be further considered carefully given the significant impact that charge trapping/detrapping at a single oxide trap may have on the behavior of a small-area MOSFET.